2012
DOI: 10.1111/j.1365-2621.2012.03207.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing constipation: a review of the laxative potential of food ingredients

Abstract: Summary Constipation is a highly prevalent and difficult‐to‐cure health problem, forcing 10–20% of the worldwide population to seek medical care. Efficacy of treatments varies greatly among individuals, and problems are becoming more frequent despite higher consumption of fibre‐rich foods, the most popular solution for preventing such gastrointestinal disorders. The evidence that consumption of fibre prevents and relieves constipation is unconvincing or uncertain. The food industry has made great efforts to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 267 publications
(229 reference statements)
0
14
0
Order By: Relevance
“…to the fiber content as well as to the presence of phytochemicals in these flours. It also seems proven the positive effect of whole-grain products consumption against constipation (Gélinas, 2013;Stewart & Schroeder, 2013). It has also been observed that the consumption of foods rich in either cereal fiber or mixtures of WGs and bran is modestly associated with a reduced risk of obesity (Cho, Qi, Fahey, George, & Klurfield, 2013;Kikuchi et al, 2018).…”
Section: No Given Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…to the fiber content as well as to the presence of phytochemicals in these flours. It also seems proven the positive effect of whole-grain products consumption against constipation (Gélinas, 2013;Stewart & Schroeder, 2013). It has also been observed that the consumption of foods rich in either cereal fiber or mixtures of WGs and bran is modestly associated with a reduced risk of obesity (Cho, Qi, Fahey, George, & Klurfield, 2013;Kikuchi et al, 2018).…”
Section: No Given Definitionmentioning
confidence: 99%
“…In general terms, all these reviews state that accumulated evidence in epidemiological studies has consistently shown that consumption of WGs is inversely associated with risk of major chronic diseases—such as certain types of cancer, type 2 diabetes, or cardiovascular disease—and these effects are attributed both to the fiber content as well as to the presence of phytochemicals in these flours. It also seems proven the positive effect of whole‐grain products consumption against constipation (Gélinas, 2013; Stewart & Schroeder, 2013). It has also been observed that the consumption of foods rich in either cereal fiber or mixtures of WGs and bran is modestly associated with a reduced risk of obesity (Cho, Qi, Fahey, George, & Klurfield, 2013; Kikuchi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fiber rich foods are attracting interest in terms of potential reduction of the glycemic response of individuals and also in the alleviation of constipation . The laxative effect of dietary fibers and fiber rich foods is well known and is associated with the water absorption capacity of dietary fibers and non‐starch polysaccharides . Fiorda et al investigated the use of protein rich flours (amaranth and cassava) in manipulating the physical properties of pasta.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fibre extracts from fruits (e.g. citrus, apples, mangoes, kiwi fruits) or vegetables (asparagus, pumpkins and mushrooms to mention a few) may also cause beneficial co-extraction of bioactive compounds, such as flavanoids and carotenoids (Bangoura et al, 2013;G elinas, 2013). Therefore, how novel and traditional fibre-enriched products perform on an acceptability level when fortifying staple foods, such as bread is of great importance for the overall performance of such products in the market place and requires more attention.…”
Section: Introductionmentioning
confidence: 99%